932. Creating a Statewide HCV Treatment Cascade for HIV/HCV Co-Infected Persons Using a Partnership with DPH. (31st December 2020) - Wegener, Maximilian D; Brooks, Ralph P; Speers, Suzanne; Villanueva, Merceditas
Abstract: Background: Treatment cascade models focused on persons with HCV mono-infection have been created based on estimates from multiple data sources. Approximately 25% of persons with HIV are coinfected with HCV; no comparable treatment cascade has been reliably generated due to inadequate HCV surveillance data. Using expanded surveillance capacity and validated HIV matching algorithms, we created an HCV treatment cascade for HIV/HCV coinfected persons in Connecticut. Methods: Surveillance databases used: CTEDSS (CT Electronic Disease Surveillance System used for HCV) and eHARS (electronic HIV/AIDS Reporting System). eHARS data timeline includes all surveillance entries with labs from 1/1/2015-10/1/2019. Two CTEDSS timelines analyzed: One, all surveillance entries (1/1/1994-1/1/2020); Two, all surveillance entries with labs from 1/1/2016-1/1/2020. Matching CTEDSS and eHARS, coinfected lists were generated and patient HCV labs (AB & PCR) were assessed to determine HCV care status on the treatment cascade. Inclusions and Exclusions for All HCV surveillance entries (1/1/1994 to 1/1/2020) Inclusions and Exclusions for All HCV Surveillance Entries with Labs from 1/1/2016 to 1/1/2020 Results: All surveillance entries (1/1/1994 to 1/1/2020): The coinfected list had 3, 689 entries; 1, 938 had positive HCV screenings (AB+ and/or PCR+) and were eligible for further analysis based on lab dispositions: 567 HCV AB+ only; 721 HCV AB+ and PCR+; 149 PCR+ only; 453 AB+ then PCR+ then PCR-; 48 PCR+ then PCR-. Of 1, 371 with evidence for chronic HCV, 501 had presumed sustained virologic response (SVR) (36.5%). All surveillance entries with HCV labs from 1/1/2016 to 1/1/2020: The coinfected list had 912 entries; 665 met inclusion criteria for positive HCV screenings with lab dispositions: 17 HCV AB+ only; 197 HCV AB+ and PCR+; 6 PCR+ only; 407 AB+ then PCR+ then PCR-; 38 PCR+ then PCR-. Of the 648 chronically infected, 445 had presumed SVR (68.6%). Treatment cascade for all surveillance entries (1/1/1994 to 1/1/2020) Treatment cascade for all surveillance entries with labs from 1/1/2016 to 1/1/2020 Conclusion: It is feasible to create statewide treatment cascades for HIV/HCV coinfected individuals. SVR rates improved from 36.5% to 68.6% with the use a of more recent HCV surveillance timeline. Contributing factors include: 2016 HCV case definition change (increased HCV PCR testing); electronic lab interface with CTEDSS being able to record negative PCRs in 2018; enhanced DAA availability and implementation. Future studies should adopt this approach which more accurately represents the HCV care status of the current co-infected population. Disclosures: All Authors : No reported disclosures